Effect of lncRNA SNHG15 on LPS-induced vascular endothelial cell apoptosis, inflammatory factor expression and oxidative stress by targeting miR-362-3p - Liu, Guanghai; Tian, Rong; Mao, Hengchao; Ren, Yanping (Cellular and Molecular Biology, 2022)
This study aimed to investigate the effect of lncRNA SNHG15 targeting miR-362-3p on LPS-induced vascular endothelial cell apoptosis, inflammatory factor expression and oxidative stress. For this purpose, human umbilical vein endothelial cells (HUVECs) were treated with 100 ng/mL LPS for 24 hours to establish a cell injury model. HUVECs were divided into control, LPS, LPS+si-NC, LPS+si-SNHG15, LPS+miR-NC, LPS+miR-362-3p, LPS+si-SNHG15+anti-miR-NC and LPS+si-SNHG15+anti-miR-362-3p groups. RT-qPCR was used to determine SNHG15 and miR-362-3pexpression. The cell inhibition rate was measured by the CCK-8 method; Cell apoptosis rate was detected by flow cytometry; the kits were employed to detect the intracellular SOD activity and the release of LDH; the ELISA method was applied to detcet the levels of TNF-α, IL-6 and IL-10 in the culture medium. Results showed that compared with the control group, the inhibition rate, apoptosis rate and SNHG15 expression level of HUVECs in the LPS group were increased (P<0.05), and the levels of TNF-α, IL-6 and LDH in the culture medium were increased (P<0.05), SOD activity, miR-362-3p expression level, and IL-10 level in the culture medium were reduced (P<0.05). The inhibition rate and apoptosis rate of HUVECs in the LPS+si-SNHG15 group were reduced (P<0.05), and the levels of TNF-α, IL-6 and LDH in the culture medium were reduced (P<0.05), SOD activity and IL-10 levels in the culture medium increased (P<0.05). The inhibition rate and apoptosis rate of HUVECs in the LPS+miR-362-3p group were reduced (P<0.05), and the levels of TNF-α, IL-6 and LDH in the culture medium were reduced (P<0.05), SOD activity and IL-10 level in the culture medium increased (P<0.05). miR-362-3p directly and bound to SNHG15. Compared with the LPS+si-SNHG15+anti-miR-NC group, the inhibition rate and apoptosis rate of HUVECs in the LPS+si-SNHG15+anti-miR-362-3p group were increased (P<0.05), and the levels of TNF-α, IL-6 and LDH in the culture medium were increased (P<0.05), and SOD activity and IL-10 levels in the culture medium were reduced (P<0.05). In general, silencing lncRNA SNHG15 inhibited LPS-induced vascular endothelial cell apoptosis, inflammatory factor expression and oxidative stress response by up-regulating miR-362-3p expression.